Blueprint to business : an entrepreneur's guide to taking action, committing to the grind, and doing the things that most people won't - Alden, Michael, 1975- (Gildan, 2019)
Bestselling author and CEO Mike Alden presents the ultimate guide to becoming a successful entrepreneur.